7-2exp(x)=0

Simple and best practice solution for 7-2exp(x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-2exp(x)=0 equation:


Simplifying
7 + -2exp(x) = 0

Multiply epx * x
7 + -2epx2 = 0

Solving
7 + -2epx2 = 0

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -2epx2 = 0 + -7

Combine like terms: 7 + -7 = 0
0 + -2epx2 = 0 + -7
-2epx2 = 0 + -7

Combine like terms: 0 + -7 = -7
-2epx2 = -7

Divide each side by '-2px2'.
e = 3.5p-1x-2

Simplifying
e = 3.5p-1x-2

See similar equations:

| 8x-12=-2(-4x+4) | | 73=-7x-3(-4x-16) | | e=6p-1x-2 | | .10+.25(n+5)=4.40 | | logx=3.6 | | 73=-7x-39(-4x-16) | | 75-10-8+12-18=x | | 5x+1/8=0.5 | | 5(x-6)=7x-6 | | exp(x)-2=4 | | 17+8=-3c-25 | | 36=5(3c-12)+4(2c+1) | | exp(7x)=8 | | 75-10-8+12=x | | 8x+4y=72 | | .10n+.25(n+6)=4.65 | | 4x+8y=72 | | F(x)=(7-2x)(x+5) | | (x^2)+x-30= | | -34+4v=6(7v+7) | | -2000000+-80000x=-3600000 | | 32-8b=-(1+2b) | | y=10x+13 | | x-23+x+89=180 | | c+t+5=415 | | -2000000+80000x=3600000 | | 96=10x-14 | | -5r-35=-6(r+6) | | 87=15x+13 | | -2(8-8x)+3=14+7x | | 2q-13=3 | | -16+9x=-34 |

Equations solver categories